Construction of a MoxC/Ni Network Electrode with Low Overpotential for Hydrogen Generation. Issue 7 (23rd May 2014) - Zhang, Jian; Meng, Xin; Zhao, Jianghong; Zhu, Zhenping
Abstract The integration of commercial photovoltaic devices and electrocatalysts has attracted considerable interest to realize the conversion of solar power to renewable hydrogen energy. However, a noble metal electrocatalyst (Pt) is too expensive and rare, which inspires the development of efficient and economical catalytic electrodes. Herein, we have fabricated a 3 D MoxC/Ni network through the carbonization of a polyaniline–Mo7O24 precursor, which was electrochemically deposited on Ni foam in advance. If the 3 D MoxC/Ni network is used as a catalytic electrode for the hydrogen evolution reaction (HER), a low onset potential of approximately 44 mV for driving 1 mA cm−2 of current density and a Tafel slope of approximately 49 mV decade−1 (overpotential η=50–60 mV) are obtained. Moreover, the apparent exchange current density reaches approximately 0.1 mA cm−2. After a long‐term HER test at η=100 mV or 500 CV sweeps, no deactivation is observed. This excellent electrocatalytic performance of the 3 D MoxC/Ni network promotes it as a promising earth‐abundant HER electrode.